Anemia in gynecology and perinatology – new attitudes - Radović-Janošević, Dragana; Čolović, Hristina; Milošević-Stevanović, Jelena; Seratlić, Jelena; Krtinić, Dane (Acta medicae Medianae, 2020)
Anemia is a global health problem. Among women, it is represented in 38% of pregnant women and 29% of non-pregnant women. The most common form is sideropenic anemia. The most common cause of anemia in gynecology is abnormal uterine bleeding that occurs as acute, chronic and intermittent bleeding. In perinatology, there are specific changes at the level of the cardiovascular and hematopoietic systems of a pregnant woman, which impose different criteria for the diagnosis of anemia relative to a non-circulating condition. The basic change is an increase in blood volume that grows more at the expense of plasma versus erythrocyte volume. The erythrocyte volume grows by about 33%, and so does the reticulocyte count. There are two basic approaches to anemia diagnosis - a kinetic approach that seeks to determine the mechanism that led to anemia and a morphological approach that divides anemia relative to the size of the erythrocyte’s mean volume and reticulocyte response. The therapy for most common - sideropenic anemia is performed with iron preparations (chemical, divalent and trivalent iron). In pregnancy, it is necessary for all pregnant women, but only in moderate doses. The total antenatal increase should be about 1000 mg. To meet these needs, 4 mg of iron per day is needed in the first half of pregnancy and 6-7 mg in the second half. Due to the poor tolerance of iron, its compliance is estimated at 50%.